2006
DOI: 10.1049/ip-syb:20050108
|View full text |Cite
|
Sign up to set email alerts
|

Decreased internalisation of ErbB1 mutants in lung cancer is linked with a mechanism conferring sensitivity to gefitinib

Abstract: A majority of gefitinib (IRESSA)-responsive tumours in non-small cell lung cancer have been found to carry mutations in ErbB1. Previously, it has been observed that internalisation-deficient ErbB1 receptors are strong drivers of oncogenesis. Using a computational model of ErbB1 trafficking and signalling, it is found that a deficiency in ErbB1 internalisation is sufficient to explain the observed signalling phenotype of these gefitinib-responsive ErbB1 mutants in lung cancer cell lines. Experimental tests conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 12 publications
1
43
0
Order By: Relevance
“…S1). As expected based on previous studies of NSCLC cells (Hendriks et al, 2006;Lazzara et al, 2010), the rate constant for EGF-mediated EGFR endocytosis (k e ) was larger in H1666 cells transduced with either of the control shRNA vectors than in corresponding PC9 cells (Fig. 1).…”
Section: Egf-mediated Egfr Endocytosis Is Promoted By Spry2 Knockdownsupporting
confidence: 89%
See 1 more Smart Citation
“…S1). As expected based on previous studies of NSCLC cells (Hendriks et al, 2006;Lazzara et al, 2010), the rate constant for EGF-mediated EGFR endocytosis (k e ) was larger in H1666 cells transduced with either of the control shRNA vectors than in corresponding PC9 cells (Fig. 1).…”
Section: Egf-mediated Egfr Endocytosis Is Promoted By Spry2 Knockdownsupporting
confidence: 89%
“…In a small fraction of NSCLCs, the expression of kinase-activated EGFR mutants confers unusual cellular sensitivity to EGFR inhibitors (Lynch et al, 2004;Paez et al, 2004;Mitsudomi and Yatabe, 2007) and leads to increased expression and phosphorylation of SPRY2 and MIG6 (Rubin et al, 2003;Guo et al, 2008;Nagashima et al, 2009). These EGFR mutations also lead to dramatic impairment of EGFR endocytosis, which has been linked to differential cellular sensitivity to EGFR inhibitors (Hendriks et al, 2006;Lazzara et al, 2010). We hypothesized that SPRY2 and MIG6 could participate in this perturbation to EGFR mutant endocytosis and in turn serve as important determinants of cellular response to EGFR inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The set of somatic mutations in the EGFR locus recently found to correlate with sensitivity to the EGFR kinase inhibitors erlotinib and gefitinib in non-small-cell lung carcinoma provide an especially interesting example [10,11]. The finding that these mutations promote prolonged activation of the EGFR led investigators to probe the trafficking properties of these mutants and find that they were significantly internalization-impaired [12]. Investigators further explored the possibility that EGFR internalization impairment might more generally lead increased cellular sensitivity to EGFR inhibition and indeed found that cells expressing WT EGFR but with low rates of EGFR internalization have increased sensitivity to gefitinib relative to WT EGFR cells with normal rates of EGFR internalization.…”
Section: Ligand/receptor Dynamics -Binding Dimerization and Traffickingmentioning
confidence: 99%
“…For example, Hendriks et al [35] have developed a differential equation model that combines a model of dimerisation of liganded receptors with a model of the consequent intracellular signalling cascade. This has been applied to model hypotheses concerning differences in the behaviour between ErbB1 receptors that are sensitive to the drug getfitinib (IRESSA), and those which are not.…”
Section: Modelling the Overall Systemmentioning
confidence: 99%